DISABILITY AN EXPERIENCE OF THE SCHOOL OF SOCIAL WORK AT THE UNIVERSITY OF COSTA RICA - Ramírez Morera, Marcela (2013)
This article describes the evaluation process of a disability course, taught in the School of Social Work at the University of Costa Rica, in mainstreaming disability issues into the curriculum of various degree programs.